Penyuluhan Hak Pasien Lanjut Usia dan Perlindungan Privasi Data Kesehatan: Upaya Peningkatan Literasi Hukum Kesehatan bagi Masyarakat Komunitas - Maya Ayu Riestiyowati; Ari Susanti; AV. Sri Suhardiningsih (Universitas Merdeka Surabaya, 2026)
Low health law literacy among the elderly and their families represents a fundamental challenge amid Indonesia's rapidly growing aging population, which reached 29.7 million individuals (11.93%) in 2025. This community service activity aimed to improve health law literacy, particularly regarding elderly patient rights under Law No. 17 of 2023 and health data privacy protection under Law No. 27 of 2022 on Personal Data Protection (PDP Law). The activity was conducted on June 9, 2026, at the Gisik Cemandi Village Hall, Sedati District, Sidoarjo Regency, involving 50 participants comprising elderly individuals aged 60 years and above along with accompanying family members. A pre-test and post-test design was employed with interactive educational sessions, and data were analyzed using a paired t-test through SPSS 25. The curriculum covered ten topics including patient information rights, informed consent, types of sensitive health data, data subject rights under the PDP Law, electronic medical records, complaint mechanisms, and the family's role as patient advocates. Results demonstrated a statistically significant improvement in mean scores, from 54.60 (SD = 12.4) at pre-test to 85.20 (SD = 9.1) at post-test (t = -7.83; df = 49; p = 0.001). The greatest improvements were observed in understanding of the PDP Law and data subject rights (+54%) also types of sensitive health data, complaint and reporting procedures (+50%). These findings confirm the effectiveness of regulation-based, interactive, and participatory health education in enhancing community health law literacy. Similar programs are recommended to be held regularly and extended to other elderly communities through cross-sector collaboration.